A MULTIMODAL DISCOURSE ANALYSIS OF DISNEYPLUS HOTSTAR INDONESIA TV ADVERTISEMENT - Intan Azkiyah; Didin Nuruddin Hidayat; Alek Alek; Ratna Sari Dewi (Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to explore the multimodal analysis of the DisneyPlus Hotstar Indonesia TV Advertisement. This research uses descriptive qualitative methods. This research data are text, symbols, images, sounds, and gestures used in DisneyPlus Hotstar Indonesia TV advertisements. The data were obtained from the DisneyPlus Hotstar Indonesia TV advertisement. Besides, the famous tagline from this advertisement is â€œPilih Semaumu, Untuk Semuaâ€ (Choose all you want, for all). The results show that DisneyPlus Hotstar Indonesia TV advertisement has a multimodal semiotic system consisting of linguistic, visual, audio, gestural, and spatial elements. Each multimodal semiotic system is closely related to constructing advertising meaning. The message is understandable for the audience. Moreover, this research is expected to contribute to developing the discourse analysis discipline, especially multimodal analysis.